Found - Haddix, Margaret Peterson (New York : Simon & Schuster Books for Young Readers, 2008)
When thirteen-year-olds Jonah and Chip, who are both adopted, learn they were discovered on a plane that appeared out of nowhere, full of babies with no adults on board, they realize that they have uncovered a mystery involving time travel and two opposing forces, each trying to repair the fabric of time
Ages 8-12
A Junior Library Guild selection
Keywords: Adoption -- Juvenile fiction; Time travel -- Juvenile fiction; Adoption -- Fiction; Time travel -- Fiction; Science fiction; Science fiction